Tyrosine kinase expressed in hepatocellular carcinoma, TEC, controls pluripotency and early cell fate decisions of human pluripotent stem cells via regulation of fibroblast growth factor-2 secretion - Vanova, Tereza; La Venuta, Giuseppe; Nickel, Walter (Stem cells, 2017)
Human pluripotent stem cells (hPSC) require signaling provided by fibroblast growth factor (FGF) receptors. This can be initiated by the recombinant FGF2 ligand supplied exogenously, but hPSC further support their niche by secretion of endogenous FGF2. In this study, we describe a role of tyrosine kinase expressed in hepatocellular carcinoma (TEC) kinase in this process. We show that TEC-mediated FGF2 secretion is essential for hPSC self-renewal, and its lack mediates specific differentiation. Following both short hairpin RNA- and small interfering RNA-mediated TEC knockdown, hPSC secretes less FGF2. This impairs hPSC proliferation that can be rescued by increasing amounts of recombinant FGF2. TEC downregulation further leads to a lower expression of the pluripotency markers, an improved priming towards neuroectodermal lineage, and a failure to develop cardiac mesoderm. Our data thus demonstrate that TEC is yet another regulator of FGF2-mediated hPSC pluripotency and differentiation. Stem Cells 2017;35:2050-2059